Chemical modification of wood fiber on the properties of polypropylene/wood fiber composites - Azieyanti Nurain Azmin
The surface of wood fiber used as reinforcement in polypropylene/wood fiber composites was modified by acrylic acid. The effect of filler loading and acrylic acid as compatibilizer on mechanical properties, water absorption and morphology was investigated.